Respuesta :
A:6.
you subtract 3x on both sides which leaves you with
6x=-36
next you divide 6 on both sides which leaves you with
x= -6
you subtract 3x on both sides which leaves you with
6x=-36
next you divide 6 on both sides which leaves you with
x= -6
Answer: The answer is A, -6.
Step-by-step explanation: To solve the equation you need to keep x on one side of the equation. So first you subtract 3x on both sides. When doing this equation you need to do the opposite of the value of the number. 3x is positive so you subtract by 3x on both sides.9x minus 3 =6x. 3x-3 equals 0, eliminating x on this side of the equation.You will then be left with 6x=-36. To solve you need to divide by 6 on both sides. 6 is being multiplied by x so you do the opposite and divide. -36 divided by 6 is equal to -6.